Effect of Live Lactobacillus acidophilus NCDC 15 and CURD as probiot ics on Blood Biochemical Profile of Early Weaned Piglets - Dhruw, Kalpana; Verma, A. K.; Agarwal, Neeta; Singh, P.; Patel, B. H. M. (International Journal of Bio-resource and Stress Management, 2015)
The present experiment was done to ascertain the effect of Lactobacillus acidophilus NCDC 15 and curd as probiotics on blood biochemical profile of early weaned piglets. A total of 36 crossbred (Landrace×Desi) piglets weaned at 28 day were assigned to three different treatments ( Control group, L. acidophilus NCDC 15 fed group, Curd fed group; n=12) each containing 4 replicates of 3 animals following completely randomized block design. Piglets of control group (first) were fed basal diet without any probiotics, while second and third groups were fed basal diet fermented with live L. acidophilus NCDC 15 (200 g day-1 piglet-1; 1.7×109 cfu g-1) and Curd (200 g day-1 piglet-1; 2.0×109 cfu g-1), respectively for a period of 120 days. The blood was collected on 0, 60 and 120 days of experimental period. The mean glucose level was significantly (p<0.01) higher in curd fed group as compared to L. acidophilus NCDC 15 fed group followed by control group. Total cholesterol level was significantly (p<0.05) lower in both the L. acidophilus NCDC 15 and curd fed group as compared to control group. The period-wise comparison of mean values of serum albumin was similar among the groups; however, period-wise comparison of total protein and globulin was significant. The results indicated that supplementation of live Lactobacillus acidophilus NCDC 15 and curd had higher glucose but low cholesterol level with similar serum protein value, which indicated good utilization of feed as well as health status of early weaned piglets.